Impact of Ambient Particulate Matter and Exposure duration on Ocular Surface Disease Severity: A Cross-Sectional Analytical Study - Fayaz Ahmed Soomro, Abdul Qadeem Soomro, Abdul Sattar, Syed Saifullah Shah, Ali Mujtaba Shah, Abdullah Laghari, Hina Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ocular surface disease particularly dry eye disease (DED) are increasingly recognized as multifactorial inflammatory disorder in which environmental exposures plays significant role. Ambient particulate matter especially in urban settings have been implicated in tear film instability and ocular surface inflammation. Objective: To evaluate the independent association between ambient particulate matter (PM2.5 and PM10), daily exposure duration, and severity of ocular surface disease measured by Ocular Surface Disease Index (OSDI). Methods: This cross-sectional analytical study included 316 adults (≥18 years) recruited from an urban population with documented particulate exposure Impact of Ambient Particulate M. Sample size was calculated using OpenEpi with 95% confidence level and 5% margin of error. Participants with active ocular infection, recent ocular surgery, autoimmune ocular disease, or contact lens use was excluded. Ambient PM2.5 and PM10 levels (µg/m³) were recorded according to exposure settings, and daily exposure duration was documented. OSDI questionnaire was used to assess symptom severity. Pearson correlation, multivariable linear regression and logistic regression analysis were performed. Results: Mean OSDI score was 39.84 ± 12.76 indicating high symptomatic burden. Significant positive correlations was observed between OSDI and PM2.5 (r = 0.121, p = 0.032), PM10 (r = 0.190, p < 0.001) and exposure duration (r = 0.191, p < 0.001). In adjusted analysis, PM10 (β = 0.052, p = 0.0046) and exposure duration (β = 0.850, p = 0.0020) remained independent predictors. PM2.5 lost statistical significance. Logistic regression showed PM10 and exposure hours independently predicts severe OSDI. Conclusion: Ambient PM10 and prolonged exposure duration are significant predictors of ocular surface disease severity. Environmental control should be considered integral part of dry eye management especially in high pollution regions. Keywords: Dry eye disease; Ocular surface disease; PM10; Air pollution; OSDI; Environmental exposure.